2017
DOI: 10.2134/jeq2016.10.0396
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Assessment of Biochar–Nitrous Oxide Mitigation Potential at the Field Scale

Abstract: Through meta-analysis, we synthesize results from field studies on the effect of biochar application on NO emissions and crop yield. We aimed to better constrain the effect of biochar on NO emissions under field conditions, identify significant predictor variables, assess potential synergies and tradeoffs between NO mitigation and yield, and discuss knowledge gaps. The response ratios for yield and NO emissions were weighted by one of two functions: (i) the inverse of the pooled variance or (ii) the inverse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 67 publications
1
49
0
Order By: Relevance
“…For this, biochar application did not generally resulted in increased soil respiration Zhou et al, 2017). Importantly, amendment of biochar had been found generally improving soil fertility and crop productivity, soil structure and moisture retention, increasing microbial abundance and metabolic efficiency of soil microbes, such as nitrobacteria and denitrobacteria related to N cycles Omondi et al, 2016;Verhoeven et al, 2017;Wu et al, 2016;Zhang, Bian, et al, 2012;Zhang, Liu, Pan, Hussain, et al, 2012;Zhou et al, 2017). In particular, BSA had been shown effective for reducing N 2 O emissions, thus improving N-use efficiency Zhang, Liu, Pan, Hussain, et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For this, biochar application did not generally resulted in increased soil respiration Zhou et al, 2017). Importantly, amendment of biochar had been found generally improving soil fertility and crop productivity, soil structure and moisture retention, increasing microbial abundance and metabolic efficiency of soil microbes, such as nitrobacteria and denitrobacteria related to N cycles Omondi et al, 2016;Verhoeven et al, 2017;Wu et al, 2016;Zhang, Bian, et al, 2012;Zhang, Liu, Pan, Hussain, et al, 2012;Zhou et al, 2017). In particular, BSA had been shown effective for reducing N 2 O emissions, thus improving N-use efficiency Zhang, Liu, Pan, Hussain, et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Given these, biochar amendment has been regarded as a hopeful measure to mitigate climate change contributed by its favorable ability in SOC sequestration and N 2 O emission reduction effects under soil amendment (Sohi, Lopez-Capel, Krull, & Bol, 2009;Woolf, Amonette, Streetperrott, Lehmann, & Joseph, 2010). Importantly, amendment of biochar had been found generally improving soil fertility and crop productivity, soil structure and moisture retention, increasing microbial abundance and metabolic efficiency of soil microbes, such as nitrobacteria and denitrobacteria related to N cycles Omondi et al, 2016;Verhoeven et al, 2017;Wu et al, 2016;Zhang, Bian, et al, 2012;Zhang, Liu, Pan, Hussain, et al, 2012;Zhou et al, 2017). Importantly, amendment of biochar had been found generally improving soil fertility and crop productivity, soil structure and moisture retention, increasing microbial abundance and metabolic efficiency of soil microbes, such as nitrobacteria and denitrobacteria related to N cycles Omondi et al, 2016;Verhoeven et al, 2017;Wu et al, 2016;Zhang, Bian, et al, 2012;Zhang, Liu, Pan, Hussain, et al, 2012;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The production of biochar and its use as a soil amendment is regarded as a promising strategy for soil carbon (C) sequestration (Lehmann, 2007) and has been shown to offer a range of agricultural benefits, such as reduced nutrient leaching (Laird et al, 2010), increased soil cation exchange (Liang et al, 2006) and water holding capacity (particularly in sandy soils) (Kammann et al, 2012). Biochar can also influence soil greenhouse gas (e.g., nitrous oxide and methane) emissions (Sagrilo et al, 2015; Verhoeven et al, 2017) and crop yields (Major et al, 2010; Schnell et al, 2012). Due to its impact on soil chemical properties, such as soil pH (Aciego Pietri and Brookes, 2008) and soil organic matter (SOM) composition (Mitchell et al, 2015), biochar can also induce shifts in soil microbial communities with important implications for a range of soil processes.…”
Section: Introductionmentioning
confidence: 99%
“…For nonindependence, Hungate et al [19] showed that the treatment of nonindependence is the most important factor in determining the difference in outcomes of similar meta-analyses, and that Sustainability 2020, 12, 3436 5 of 14 strict versus relaxed nonindependence criteria can significantly affect results. Therefore, the inverse of the number of observations per site (referred to as site-weighted) is determined for the control of nonindependence [20]. For example, if we only want to explore the effect of biochar types on soil GHG emissions, then the biochar application rate is nonindependent.…”
Section: Meta-analysismentioning
confidence: 99%
“…Recently, many researchers explored the effects of biochar application on soil GHG emissions by using systematic reviews such as meta-analysis [9,[18][19][20]. Cayuela et al [21] only emphasized the role of biochar in the mitigation of soil N 2 O emission on the basis of 30 studies with 261 treatments.…”
Section: Introductionmentioning
confidence: 99%